2006
DOI: 10.1016/j.ejcts.2005.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Relation of inflammatory cytokines to atrial fibrillation after off-pump coronary artery bypass grafting

Abstract: Advanced age was a major risk factor for postoperative AF. Furthermore, inflammatory response induced by surgical trauma was also associated with the development of AF after off-pump CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 24 publications
7
72
3
8
Order By: Relevance
“…9,10) CRP can be used to measure systemic inflammation in clinical settings. 8,11,12) In this study, the postoperative mean peak CRP level was higher in patients who developed postoperative atrial fibrillation (168.3 ± 29.1 mg/L versus 112.6 ± 19.6 mg/L in patients without atrial fibrillation, P < 0.0001), and logistic regression analysis showed postoperative CRP levels above the median value were associated with increased risk of postoperative atrial fibrillation (2.421, P = 0.015). This study further confirmed the importance of inflammation in the development of atrial fibrillation following CCABG.…”
Section: Discussionmentioning
confidence: 48%
“…9,10) CRP can be used to measure systemic inflammation in clinical settings. 8,11,12) In this study, the postoperative mean peak CRP level was higher in patients who developed postoperative atrial fibrillation (168.3 ± 29.1 mg/L versus 112.6 ± 19.6 mg/L in patients without atrial fibrillation, P < 0.0001), and logistic regression analysis showed postoperative CRP levels above the median value were associated with increased risk of postoperative atrial fibrillation (2.421, P = 0.015). This study further confirmed the importance of inflammation in the development of atrial fibrillation following CCABG.…”
Section: Discussionmentioning
confidence: 48%
“…Ishida, et al 50) examined the relationship between proinflammatory cytokines, which play an important role in the upstream regulation of inflammatory cascades, and the development of AF after OPCAB in a 39 patients' case series. Eleven patients (28%) developed AF postoperatively.…”
Section: Postoperative Atrial Fibrillation (Af)mentioning
confidence: 99%
“…Considering inflammatory processes involved in postoperative AF, the markers of inflammation may be of importance in diagnosing and/or risk stratification of such patients. Accordingly, Ishida et al [22] have noted that C-reactive protein (CRP), interleukin-6 (IL-6) and IL-8 increased after off-pump CABG surgery, but IL-6 was only significantly different between patients with and without postoperative AF, and it was an independent predictor of postoperative AF occurrence. Patients with an increased baseline CRP value have also been found to be in higher risk for developing AF after on-and off-pump CABG surgery [23].…”
Section: Discussionmentioning
confidence: 99%